2021
DOI: 10.3390/children8020135
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Children and Adolescents during COVID-19 Pandemic

Abstract: Background: The COVID-19 pandemic has led to special circumstances and changes to everyday life due to the worldwide measures that were imposed such as lockdowns. This review aims to evaluate obesity in children, adolescents and young adults during the COVID-19 pandemic. Methods: A literature search was conducted to evaluate pertinent studies up to 10 November 2020. Results: A total of 15 articles were eligible; 9 identified 17,028,111 children, adolescents and young adults from 5–25 years old, 5 pertained to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
149
3
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(192 citation statements)
references
References 30 publications
11
149
3
11
Order By: Relevance
“…The results of this study showed an increase in the rate of unhealthy weight gain during the pandemic compared to the rate before the pandemic. This is likely, in part or in whole, a result of the pandemicrelated lifestyle changes reported in previous literature [17] (including decreased physical activity [ 18 , 19 ], changes in diet composition [20] , and increased indoor sedentary behaviors [19] ). The findings are consistent in direction to predictions made by a simulation study [21] .…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed an increase in the rate of unhealthy weight gain during the pandemic compared to the rate before the pandemic. This is likely, in part or in whole, a result of the pandemicrelated lifestyle changes reported in previous literature [17] (including decreased physical activity [ 18 , 19 ], changes in diet composition [20] , and increased indoor sedentary behaviors [19] ). The findings are consistent in direction to predictions made by a simulation study [21] .…”
Section: Discussionmentioning
confidence: 99%
“…While these decreases in snacking may be observed, excess weight gain will likely still need to be addressed. A recent review of 15 studies on obesity in children during the pandemic found support for an increase in child weight, which was associated with changes in eating habits and limited physical activity [ 35 ]. For parents, who may find themselves in work situations that combine office and remote work, changing snacking behaviors may be more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our research, with 33 % overweight and obese students, are on the same ascending trajectory as the results reported by the above studies. Due to the amplitude of the phenomenon a new term 'covibesity' has appeared to synthesize the increment in obesity rates due to restriction imposed during the pandemic [14].…”
Section: Discussionmentioning
confidence: 99%